Efficacy of plant extract in chronic low back pain: A meta-analysis - Chen-Pi Li; Ru-Yin Tsai; Jui-Ting Yu; Shin-Chuan Huang; Fang-Ling Liu; Sheng-Yi Lin (Tungs’ Medical Journal)
Background: Chronic low back pain (CLBP) impacts quality of life and healthcare reliance. Objectives: We systematically reviewed randomized controlled trials (RCTs) on the use of plant extracts to treat CLBP according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Methods: Four databases (i.e., PubMed, Scopus, Web of Science, and The Cochrane Library) were searched for published studies. We searched databases up to July 2024. Seven RCTs were analyzed. The study has been registered in PROSPERO (number: CRD 42024570674). Results: Plant extracts alone or combined with massage significantly reduced pain, particularly when applied to multiple meridian points. Conclusion: Plant extracts are a promising nonpharmacological treatment option for CLBP. One potential mechanism is through their interaction with multiple meridian pathways, which may enhance pain relief. This possible relationship between meridian involvement and therapeutic efficacy warrants further investigation to better understand the long-term benefits and underlying mechanisms of plant extract therapy.